Utilizacion de la yuca - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
The factors affecting the quality of cassava roots were studied: var. and age of the plant; DM, starch, and sugar contents in the roots; cyanide contents in leaves and roots. Roots of bitter var. CMC-84 showed higher DM contents than those of sweet var. CMC- 40. Total and reducing sugar contents followed slightly different trends throughout the 9-12 mo. period in both var. Total cyanide content in CMC-84 was less affected by age than that of CMC-40; root parenchyma tissue had moreless stable total cyanide content in both var. Expt. were conducted on the effect of drying cassava on concrete floors and on inclined trays on HCN elimination. Both methods efficiently reduced HCN levels for animal feeding. Sun drying on trays and oven drying were compared. For all var., oven drying at 60 degrees Celsius produced dried chips with a lower HCN content (p less or equal to 0.05). The silage process of CMC-40 reduced total cyanide content to 25-36 percent of the initial concn. after 6 mo. Piglet preference for diets containing 0, 14, 20, 28, and 40 percent CM was studied and a consistent preference was found for diets containing 28 and 40 percent CM. In 1 expt. 53percent of the total feed consumed contained 40 percent CM. In expt. carried out with broilers, results indicated that CM can be used up to 20 percent without causing nutritional problems. Preliminary information was also obtained on cassava processing for the animal feed market on the north coast of Colombia, through a pilot collaborative project carried out by the Integrated Rural Development Program (DRI), the Canadian International Development Agency, and CIAT. (CIAT)